The Selfish Crocodile - Charles, Faustin (Waukesha, WI Little Tiger Press, 1999)
Everyday a selfish crocodile warns the animals to stay away from the river. But when the crocodile finds himself in trouble, a verybrave and unlikely hero teches him a valuable lesson.
Keywords: Crocodiles -- Fiction; Mice -- Fiction; Attitude -- Fiction; Animals -- Fiction